The Patriarchate of Constantinople and the Orthodox Diaspora in the 20th century: polemics around the creation of an Exarchate of the Russian Orthodox Churches in Western Europe - Vladislav Puzovich (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2014)
The author considers the historical circumstances of the creation of the Exarchate of the Russian Orthodox Churches under the jurisdiction of the Patriarchate of Constantinople in Western Europe in 1931. This event was a crucial one for the fates of the Orthodox Diaspora in the 20th century. It exempliﬁed two ecclesiological concepts bearing on the role of the Patriarchate of Constantinople in the Orthodox Diaspora ascribed to it by the participants of the discussion. The ﬁrst of these concepts maintains that only the patriarchate of Constantinople has the right of jurisdiction over the Orthodox Diaspora, while the second one rules this necessity out and emphatically states that the jurisdiction over their respective Diasporas should be exercised by the national Churches. The opposition of these two concepts has become a characteristic trait of the Orthodox history in the 20th century.